The Determinants of Indonesian Muzakki’s Decision to Pay Zakat through Zakat Institutions - Febrianti, Lutfia Adha; Noor, Iswan (International Journal of Zakat, 2024)
The aim of this research is to analyze four factors that are thought to influence the muzakki's decision to carry out zakat payments through zakat institutions, namely transparency, accountability, service quality and muzakki income. Researchers used quantitative methods with Structural Equation Model Partial Least Square (SEM-PLS) analysis. The number of respondents involved in this research was 124 respondents. The results of the analysis show that the variables transparency, service quality and muzakki's income have a significant positive effect on muzakki's decision to carry out zakat payments through zakat institutions. Meanwhile, the accountability variable does not have a significant influence on the muzakki's decision to carry out zakat payments through zakat institutions. It is hoped that this research can become an additional reference for the government, zakat institutions and academics in an effort to increase muzakki's trust in zakat institutions. Efforts that can be made are to pay attention to aspects of institutional transparency and accountability, namely by actively publishing financial reports and distributing zakat funds. In this way, existing zakat funds can be utilized optimally.